Investigation Of The Properties Of The Developed Composite Chemical Flotation Reagents And Their Application In The Flotation Process (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Paper Considers The Results Of Studying The Chemical Composition And Physicochemical Properties Of Ore And A Number Of Organomineral Ingredients Based On Local Raw Materials And Production Wastes For The Development Of Composite Flotation Reagents-Foaming Agents. A New Flotation Reagent-Foaming Agent, Conventionally Designated "KHF-VS", Is Synthesized, Similar To The Russian-Made T-92. The Results Of Physicochemical Studies Of The Developed Flotation Reagents-Foaming Agents Are Presented, And On Their Basis Effective Compositions For Use In The Process Of Ore Flotation Have Been Developed. To Compare The Sorption Properties Of The Developed Composite Flotation Reagents-Foaming Agents Of The Kkhf-VS Class With A Traditional Foaming Agent - T-92, We, Together With The Employees Of Almalyk Mining And Metallurgical Combine (AGMK), Conducted Tests In Laboratory Production Conditions. According To The Results Of The Experiments, The Best Indicators Were Obtained Using The Sample KHF-VS-1, The Extraction Of Copper In The Rough Concentrate Consisted Of 91.35% With A Quality Of 6.74% Copper.